2009
DOI: 10.1007/s10971-009-2122-z
|View full text |Cite
|
Sign up to set email alerts
|

Template-free synthesis of hierarchical porous SnO2

Abstract: Hierarchical porous tin dioxide has been successfully prepared through a fast one-pot template-free synthesis route. The boiling of the mixture of alcohol and glycerol can be utilized to generate nanopores in the SnO 2 monolith. Polycrystalline hierarchical SnO 2 with well proportioned composition has also been obtained in the pore walls of tin dioxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Thus, the region of O 1s could be deconvoluted into three peaks centered at 530.3, 530.8, and 531.5 eV. The lower binding energy peak at 530.3 eV was attributed to oxygen in SnO 2 , , while the peak centered at 530.8 eV is due to the Zn–O binding . The peak at 531.5 eV could be ascribed to adsorbed hydroxyl species. ,, The results confirmed that the SnO 2 –ZnO photocatalyst was actually composed of SnO 2 and ZnO entities.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Thus, the region of O 1s could be deconvoluted into three peaks centered at 530.3, 530.8, and 531.5 eV. The lower binding energy peak at 530.3 eV was attributed to oxygen in SnO 2 , , while the peak centered at 530.8 eV is due to the Zn–O binding . The peak at 531.5 eV could be ascribed to adsorbed hydroxyl species. ,, The results confirmed that the SnO 2 –ZnO photocatalyst was actually composed of SnO 2 and ZnO entities.…”
Section: Resultsmentioning
confidence: 57%
“…The lower binding energy peak at 530.3 eV was attributed to oxygen in SnO 2 , , while the peak centered at 530.8 eV is due to the Zn–O binding . The peak at 531.5 eV could be ascribed to adsorbed hydroxyl species. ,, The results confirmed that the SnO 2 –ZnO photocatalyst was actually composed of SnO 2 and ZnO entities. To determine the band alignment of the SnO 2 –ZnO nanocatalyst, the core level positions and the VBM positions of bulk SnO 2 and bulk ZnO were also determined .…”
Section: Resultsmentioning
confidence: 63%
“…It is also usually suggested that the binding energies of Sn 3d5/2 and Sn 3d3/2 are usually located at 486.4 eV and 495.0 eV, respectively. 43,46 Both of the binding energies of Sn 3d5/2 and Sn 3d3/2 in the ternary heterostructures slightly shift by 0.2 eV toward low energy, also demonstrating the possibly increased surface electron density of SnO 2 by construction of the ternary heterostructures. The nitrogen adsorption-desorption isotherm and the corresponding pore size distribution of TiO 2 /SnO x -Au (1 wt%) and TiO 2 /Au (1 wt%) are shown in Fig.…”
Section: Resultsmentioning
confidence: 88%
“…3d. In this spectrum, the coupling peaks appearing at 530.2 eV and 530.7 eV are attributed to oxygen at the Sn-O and Zn-O bonds, respectively [57,58].…”
Section: Surface Chemical Compositionmentioning
confidence: 97%